Main Trends in the Development of Russian Law on Non-Profit Organizations - A. Avtonomov; V. Grib (BRICS Law Journal, 2020)
The article is a comparative study of legal regulation on non-profits in the Russian Federation by federal law, including the Constitution, federal statutes, decrees of the President of the Russian Federation, resolutions of the Government and Constitutional Court rulings in connection with certain international legal acts dealing with the right to association, and by the law of the constituent entities of the Russian Federation. The main stages of the development of the law on non-profits both at the federal level and at the level of the constituent entities of the Russian Federation, as well as the main trends in the development of non-profit law in modern Russia, are explored.